Pengaruh Produk, Harga, Dan Word Of Mouth Terhadap Kepuasan Konsumen Pada Waroeng Steak And Shake Di Kota Bandar Lampung - Ridho Aldanis; Aida Sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study investigates the influence of product, price, and word of mouth on customer satisfaction at Waroeng Steak and Shake in Bandar Lampung. The food and beverage industry in Indonesia has experienced significant growth, with the sector expanding by 5.53% in Q2 2024 and contributing the largest share to the national GDP. In this competitive environment, understanding the factors affecting customer satisfaction is crucial for business sustainability. The research employed a quantitative approach with multiple linear regression analysis on 109 respondents selected through purposive sampling. Data were collected using questionnaires with a Likert scale and analyzed using IBM SPSS Statistics version 25. The results indicate that all three variables significantly affect customer satisfaction. Word of mouth has the strongest influence (β = 0.648; p < 0.001), followed by price (β = 0.189; p = 0.005) and product (β = 0.104; p = 0.001). The coefficient of determination (R² = 0.728) shows that 72.8% of the variance in customer satisfaction can be explained by these three variables. These findings suggest that restaurant management should prioritize enhancing positive word of mouth through excellent service experiences, maintaining competitive pricing strategies aligned with perceived value, and ensuring consistent product quality to improve customer satisfaction.